Analisis Alih Kode dalam Novel “Senja & Pagi” Karya Alffy Rev - Putri Wahyu Ramadani; Ita Kurnia; Lutfia Putri Wahyuningtyas (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This study analyzes code switching and code mixing in the novel "Senja&Pagi" by Alffy Rev. The aim of research on code-switching in languages is to understand and analyze the phenomenon of using more than one language or variations of languages in certain conversations or communication contexts. There is an external form of code switching in the form of language switching which includes: a) Indonesian to Arabic switching and b) Indonesian to English switching, and there is also internal code switching, namely c) Indonesian to Javanese switching. In the novel "Senja & Pagi" by Alffy Rev there are factors that cause code switching due to the presence of a speaker or speakers, interlocutors or listeners, changes in subject matter and topics of conversation.